Disturbances in selective information processing associated with the BDNF Val66Met polymorphism: Evidence from cognition, the P300 and fronto-hippocampal systems - Schofield, Peter R.; Williams, Leanne M.; Paul, Robert H.; Gatt, Justine M.; Brown, Kerri; Luty, Agnes; Cooper, Nicholas; Grieve, Stuart; Dobson-Stone, Carol; Morris, Charlotte; Kuan, Stacey A.; Gordon, Evian (Biological psychology, 2009)
In this study, we examined whether the Met allele of the BDNF Val66Met polymorphism is associated with selective disruptions to task-relevant information processing. In 475 non-clinical participants for whom BDNF genotype status was determined we used the ‘IntegNeuro’ computerized battery of neuropsychological tests to assess cognitive performance, an auditory oddball task to elicit the P300 event-related potential (ERP) and, in smaller subsets of these subjects, high resolution structural MRI imaging to quantify fronto-hippocampal grey matter ( n = 161), and functional magnetic resonance imaging to assess fronto-hippocampal BOLD activation ( n = 37). Met/Met (MM) homozygotes had higher verbal recall errors, in the absence of differences in attention, executive function, verbal ability or sensori-motor function. Further, MM homozygotes demonstrated a slowed P300 ERP during the oddball task, with corresponding alterations in hippocampal and lateral prefrontal activation, and a localized reduction in hippocampal grey matter. These results are consistent with a subtle impact of the Met allele on fronto-hippocampal systems involved in selective information processing of stimulus context and memory updating within the normal population. The findings also indicate that heritable endophenotypes such as the P300 have value in elucidating genotype–phenotype relationships.